Many Ways to Internalize Islamic Values Implemented in Indonesia - Khairiah, Nalil; Nurzannah, Nurzannah (Budapest International Research and Critics University, 2020)
The background of this study is the abuse of public trust in officials and state officials both national and local level. It can be seen from the various corrupt cases done by public officials. Since 2004-2013, it has been revealed at least 291 district head from provincial or even city. Therefore, as a prevenentative measure for the younger generation, especially for students who will be future leaders need to be instilled the values of good governance, so that they can manage the country well.Students as a group of public intellectuals are expected to be an agent of change, because the mission and functions of higher education is to protect and strengthen social values to train students in order to form the basis of democratic citizenship and internalize the values of good governance through Islam. The research method is the result of research development modules. The data collection was done by Focus Group Discussion lecturers subjects citizenship and Islamic Studies, interview, test and training result. The results showed that to instill the values of good governance required courses individually or custom. During this time students understand the concept of good governance from civic education as well as citizenship. In addition, to facilitate the understanding of the values of good governance, Islamic approach as an alternative to socialize good governance.